2020
DOI: 10.1016/j.urology.2020.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diffusion-Weighted Magnetic Resonance Imaging in the Diagnosis of Bladder Pain Syndrome/Interstitial Cystitis

Abstract: To evaluate whether DW-MRI can contribute to noninvasive diagnosis of BPS/IC. The agreement between two raters (2 radiologists involved in the study) was also evaluated, the relevance of the "operator-dependent" factor defined. PATIENTS AND METHODS Twenty-two female patients with a diagnosis of BPS-IC were recruited and performed DW-MRI. The same investigation was also performed in 20 patients with pelvic gynecological diseases and no BPS-IC. RESULTS A significant difference was found between BPS-IC and no-BPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Since the discovery of Huuner's lesion more than 100 years ago, patients with IC/BPS had generally underwent cystoscopy, urodynamic study, and biopsy for histopathology, with radiological examinations for gross bladder morphology being rare. Several recent pilot studies, however, have utilized MRI to evaluate bladder wall changes in patients with IC/BPS [11][12][13]. Although evidence had suggested that MRI could be used for noninvasive diagnosis of IC/BPS, the association between clinical characteristics and abnormal findings have yet to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of Huuner's lesion more than 100 years ago, patients with IC/BPS had generally underwent cystoscopy, urodynamic study, and biopsy for histopathology, with radiological examinations for gross bladder morphology being rare. Several recent pilot studies, however, have utilized MRI to evaluate bladder wall changes in patients with IC/BPS [11][12][13]. Although evidence had suggested that MRI could be used for noninvasive diagnosis of IC/BPS, the association between clinical characteristics and abnormal findings have yet to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, diffusion-weighted MRI (DW-MRI) or DWI has been used for the diagnosis of IC/BPS, where a high DW-MRI signal was found to be substantially higher in IC patients compared to normal controls [ 50 , 51 ]. They suggested that having a positive DW-MRI signal was suggestive of IC [ 50 ].…”
Section: Mri Imagingmentioning
confidence: 99%
“…Recently, diffusion-weighted MRI (DW-MRI) or DWI has been used for the diagnosis of IC/BPS, where a high DW-MRI signal was found to be substantially higher in IC patients compared to normal controls [ 50 , 51 ]. They suggested that having a positive DW-MRI signal was suggestive of IC [ 50 ]. Unfortunately, in either study, they did not specifically measure the apparent diffusion coefficient (ADC), which should increase with increased inflammation, however, which may also contribute to calculation errors if low b-values are used which also takes into consideration the effect of perfusion [ 52 ].…”
Section: Mri Imagingmentioning
confidence: 99%
“…Since Yang performed MRI scans on patients with pelvic floor dysfunction for the first time in 1991, with the development and updating of MRI machines and imaging techniques, pelvic floor MRI has gradually developed from static MRI, dynamic MRI, and functional MRI [ 7 ]. Combining a variety of MRI imaging techniques can not only help diagnose and analyze the changes of the three-chamber pelvic floor in real time, but also discover the changes and damage of anatomical structures under different pathological conditions and explore the pathogenesis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%